Transforming Management of Islamic Educational Institutions in Indonesia: Concepts, Strategic Shifts, and Implementation Challenges - Moh. Mundzir (AL-TAHRIR, 2025)
slamic education plays a strategic role in building a civilization based on divine values, morality, and humanity. In the era of globalization and the Fourth Industrial Revolution, Islamic educational institutions are required to undergo managerial transformation to remain relevant and competitive. This study employs a qualitative approach with a descriptive-analytical method to analyze the concepts, strategies, and implementation of contemporary Islamic education management transformation. Data were collected through library research and document analysis from various sources such as books, scholarly journals, and institutional reports, then analyzed through the stages of reduction, categorization, presentation, and conclusion drawing, with expert validation to ensure data credibility. The results show that the transformation of Islamic education management encompasses three main dimensions: governance reform based on the principles of good governance, strengthening human resource capacity oriented toward digital and pedagogical competencies, and integrating technology into administrative and learning systems. The strategies that can be applied include the digitalization of educational administration, the development of Islamic value-based leadership, and the integration of religious and modern sciences within the curriculum. Although several challenges exist, such as resistance to change, limited resources, and complex regulations, development opportunities arise through the utilization of digital technology and cross-institutional collaboration. Ultimately, the transformation of Islamic education management must be sustainable through a holistic approach that combines spirituality, professionalism, and innovation to produce an excellent, ethical, and adaptive generation. The implications of this research provide theoretical contributions to the development of Islamic education management concepts and practical recommendations for policymakers and institutional leaders in designing effective and future-oriented transformation strategies.